"I truly think that some schools don't want to appear as if they have these issues." - Kate Cole; Tanya Surette (Canadian Society for Studies in Education, 2024)
Queer educators experience their work differently than their non-queer colleagues due to institutional and systemic pressures and influence. Due to tokenism and routine microaggressions, as well as implicit pressure to lead anti-oppressive practices at multiple school levels, these educators routinely experience marginalization and oppression in their work. This research invited four 2SLGBTQIA+ educators to share rich storied descriptions of their experiences within educational spaces. The study employed qualitative analysis through a narrative inquiry-based lens of the lived experiences of these Canadian educators. The results of the narrative analysis revealed a series of shared experiences of a variety of oppressions that were categorized as institutional, personal, and actionable. Results showed shared experiences of tension between systemic expectations and treatment with participant's needs and wellbeing. As foundational work, this research illuminated gaps in the nuanced understanding of the experiences of queer educators in Canadian school contexts.